Tafamidis improves myocardial longitudinal strain in A97S transthyretin cardiac amyloidosis - Yuan-Kun (Aden); An-Li Yu; Mei-Fang Cheng; Lung-Chun Lin; Ming-Jen Lee; Chia-Hung Chou; Chia-Tung Shun; Hsueh-Wen Hsueh; Jimmy Jyh-Ming Juang; Ping-Huei Tseng; Siao-Ping Lin; Mao-Yuan Su; et al. (SAGE Publishing, 2024)
Background: Transthyretin cardiomyopathy (ATTR-CM) is a debilitating disease that has received much attention since the emergence of novel treatments. The Transthyretin Cardiomyopathy Clinical Trial showed that tafamidis, a transthyretin tetramer stabilizer, effectively reduced the declines in functional capacity and quality of life. However, Ala97Ser (A97S) hereditary ATTR-CM is underrepresented in major ATTR-CM tafamidis trials. Objectives: We aim to investigate the change in global longitudinal strain (GLS) of A97S ATTR-CM patients after 12 months of tafamidis treatment. Methods: We retrospectively analysed a prospective cohort of patients with A97S ATTR-CM who received tafamidis meglumine (61 mg/day) at the National Taiwan University Hospital. Echocardiography with speckle tracking strain analysis was performed at baseline and 12 months after treatment. Results: In all, 20 patients were included in the cohort. The baseline left ventricular ejection fraction (LVEF) and interventricular septum (IVS) thickness were 59.20 ± 13.23% and 15.10 ± 3.43 mm, respectively. After 12 months of tafamidis treatment, the LVEF and IVS were 61.83 ± 15.60% ( p  = 0.244) and 14.59 ± 3.03 mm ( p  = 0.623), respectively. GLS significantly improved from −12.70 ± 3.31% to −13.72 ± 3.17% ( p  = 0.048), and longitudinal strain (LS) in apical and middle segments significantly improved from −16.05 ± 4.82% to −17.95 ± 3.48% ( p  = 0.039) and −11.89 ± 4.38% to −13.58 ± 3.12% ( p  = 0.039), respectively. Subgroup analysis showed that patients with LVEF < 50% had a better treatment response and improvement in GLS. The patients with an IVS ⩾ 13 mm had an improvement in two-chamber LS from −10.92 ± 4.25% to −13.15 ± 3.87% ( p  = 0.042) and an improvement in apical left ventricular LS from −15.30 ± 5.35% to −17.82 ± 3.99% ( p  = 0.031). Conclusion: Tafamidis significantly improved GLS, and particularly apical and middle LS in A97S ATTR-CM patients.